On the deployment of thermoelectric waste heat recovery in the Malaysian road transport sector - Saqr, Khalid M.; Musa, Md. Nor (Universiti Teknologi Malaysia, Johor, Malaysia, 2008)
The road transport sector in Malaysia consumes the major portion of energy consumed by all transportation sectors, which represents 63% of the total energy consumption along with industrial sector as of 2005. While in 2002, energy demand for road transport represented 86 % of the total transport energy demand. Indisputably, more than 60% of the fuel energy is lost as waste heat in ICE driven vehicles. This enormous percentage of waste fuel energy charges Malaysia billions of MYR every single year due to the escalating reliance on road transport. Automotive OEM and several research organizations worldwide have been focusing on TWHR systems as possible solutions to recover such huge amounts of waste fuel energy. This paper focuses on investigating the potential energy savings from deploying TWHR systems in the Malaysian road transport sector as well as exploring the prospective investment size.